Comparing depression, anxiety, and quality of life in individuals with cardiac and non-cardiac chest pain - Zarean, Elham; Samani, Zahra Bahrami; Kheiri, Soleiman; Torkian, Samaneh (Frontiers in Psychiatry, 2024)
Background Psychological factors are often overlooked as potential contributors to cardiovascular disease. This study aimed to investigate the relationship between depression, anxiety, and quality of life with chest pain origin. Method This cross-sectional study was performed from 2019 to 2020 and included participants from multiple medical centers across Shahrekord, Iran. Participants were recruited through advertisements in medical centers. Participants were divided into three groups: healthy control (n = 67), chest pain with cardiac origin (CCP) (n = 70), and chest pain with non-cardiac origin (NCCP) (n = 73). Data were collected using the Beck’s Anxiety scale, Beck’s Depression scale, and Short-Form Health Survey questionnaires. The chi-square, exact test, t-test, Kruskal–Wallis, and logistic regression models were used for statistical analysis. All analysis was performed using SPSS 26. Results The mean scores of depression and anxiety in the NCCP group (depression = 17.03 ± 11.93, anxiety = 17.18 ± 11.37) were significantly higher than those in the CCP (depression = 9.73 ± 5.76, anxiety = 8.77 ± 5.96) and healthy (depression = 7.00 ± 7.61, anxiety = 6.18 ± 7.63) groups (p < 0.05). The mean score of quality of life in the NCCP group (54.87 ± 12.66) was significantly lower than that in the CCP (76.31 ± 12.49) and healthy (80.94 ± 15.78) groups (p < 0.05). Patients with NCCP had higher odds of having depression (adjusted OR = 4.39, 95% CI: 1.25, 15.35) and lower odds for having mental quality of life scores than the CCP and health groups, respectively (adjusted OR = 0.90, 95% CI: 0.87, 0.94). Conclusion Our findings suggest that collaboration between psychiatrists and other specialists may be necessary to improve patients’ health conditions and quality of life.